2001
DOI: 10.1063/1.1404998
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic contact formation mechanism of Ni on n-type 4H–SiC

Abstract: Ohmic contact formation mechanism of Ni on n-type 4H–SiC is proposed by comparing the electrical properties with microstructural change. The ohmic behavior was observed at temperatures higher than 900 °C, but Ni2Si phase, as formerly reported to be responsible for ohmic contact, was formed after annealing at 600 °C. The higher work function of Ni2Si than Ni and the observation of graphite phase on the surface of Ni silicide after annealing at 950 °C support that a number of carbon vacancies were produced below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(76 citation statements)
references
References 10 publications
4
72
0
Order By: Relevance
“…13,18,23 Besides, creating vacancies at interface region to improve the nature of interface with Ohmic contact, low Schottky Barrier and high electronic transparency have been used in many metal-semiconductors contacts. 26,27 Thus, the formation of vacancy defects in monolayer MoS 2 is a possible method to achieve high quality Au-MoS 2 contact with Ohmic character.…”
Section: 22mentioning
confidence: 99%
“…13,18,23 Besides, creating vacancies at interface region to improve the nature of interface with Ohmic contact, low Schottky Barrier and high electronic transparency have been used in many metal-semiconductors contacts. 26,27 Thus, the formation of vacancy defects in monolayer MoS 2 is a possible method to achieve high quality Au-MoS 2 contact with Ohmic character.…”
Section: 22mentioning
confidence: 99%
“…Actually, Han et al [3,4,8] and Kuchuk et al [9] indicated the presence of NiSi right above the C1 band for 950°C annealing and at the substrate interface for 1050°C annealing, respectively. Probably, the NiSi/4H-SiC system might be lower in φ B than the Ni 2 Si/4H-SiC system.…”
Section: Materials Science Forum Vols 679-680 467mentioning
confidence: 99%
“…This steep temperature dependence of ρ C for contacts in the n++ region cannot be explained by the carbon vacancy induced donor model (Vc model) proposed by Han and his coworkers [3,4] because heavy doping eclipses the increased donor effect. Figure 3 shows the interface between the Ni-slicide and the epilayer (n++ region) captured by high-resolution XTEM, when the Ni (TLM) electrode was annealed at 1000°C.…”
mentioning
confidence: 99%
“…As a candidate material for micro or nano-electronics, the nickel silicide formed at the Ni-SiC interface could provide lowresistivity metal contact and interconnect [21][22][23] between the semiconducting SiC whisker and the carbon nanotube. The contact or interconnect quality here should be further investigated by adjusting the reaction temperature and time, the yield of the silicides and the quantity of residual catalysts at the connecting areas.…”
Section: Ni-w-p Catalyzed Growth Of Carbon Nanotubes On Sic Whiskersmentioning
confidence: 99%